Retrospective analysis of autoimmune bullous diseases in Middle Franconia - Sollfrank, Lukas; Schönfelder, Valerie; Sticherling, Micheal (Frontiers in Immunology, 2023)
Autoimmune bullous diseases (AIBDs) are a group of rare cutaneous disorders affecting cornified skin and mucous membranes. They are characterized by tense or flaccid blistering and erosions due to autoantibodies against desmosomal and hemidesmosomal structural proteins of the skin. This group of disorders can be divided into those of pemphigoid and those of pemphigus diseases. If left untreated, these autoimmune diseases can cause serious or even life-threatening complications such as loss of fluid, superinfections or impaired food intake.Due to modern standardized serological assays, the diagnosis of AIBDs can usually be confirmed in combination with their clinical appearance. Whereas for a long time corticosteroids were the major players in the treatment of these diseases, with the approval of rituximab and other immunosuppressive agents, the therapy has increasingly improved. In this study, we aimed to investigate epidemiologic and clinical features as well as diagnostics and therapy of bullous autoimmune diseases in Middle Franconia, a governorate within the German federal state of Bavaria. Patients diagnosed or treated because of a AIBDs between 01.04.2013 and 31.03.2019 at the dermatological department of the university hospital Erlangen were included in this retrospective study (n = 242). Patients were either diagnosed for the first time (n=176) or the diagnosis has been confirmed (n=66) at the department. The respective incidence was calculated among the 176 subjects who had been diagnosed at the center in this period. Data was taken from patient records and analyzed with Micorsoft® Excel.The evaluation included the diagnoses of pemphigus vulgaris (PV), pemphigus folliaceus (PF), bullous pemphigoid (BP), mucous membrane pemphigoid (MMP), linear IgA dermatosis (LAD), epidermolysis bullosa acquisita (EBA), and dermatitis herpetiformis (DH). This study shows that the incidence of each AIBDs in Middle Franconia is low and comparable (PV, PF, LAD, EBA) or lower (BP, MMP, DH) than in other studies and regions. BP is the most common newly diagnosed AIBD in Middle Franconia. Due to the chronic and sometimes severe course of AIBDs, repeated in-house treatments are often necessary. To date, mainly topically and systemically applied corticosteroids in combination with immunomodulators are used as firstline therapy.